1996
DOI: 10.1021/ic960403t
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Atom Transfer, Sulfur Atom Transfer, and Correlated Electron−Nucleophile Transfer Reactions of Oxo- and Thiomolybdenum(IV) Complexes:  Synthesis of Oxothiomolybdenum(VI) and (Hydroxo)oxomolybdenum(V) Species

Abstract: Reaction of Mo IV O(S 2 PR 2 ) 2 with K{HB(Pr i pz) 3 } [HB(Pr i pz) 3 -) hydrotris(isopropylpyrazol-1-yl)borate] in refluxing toluene affords green L*Mo IV O(S 2 PR 2 -S,S′) complexes [L* ) HB(3-Pr i pz) 2 (5-Pr i pz) -) hydrobis(3-isopropylpyrazol-1-yl)(5-isopropylpyrazol-1-yl)borate; R ) Pr i , Ph], which are converted upon reaction with boron sulfide in dichloromethane to the yellow thio analogues L*Mo IV S(S 2 PR 2 -S,S′). Crystals of L*Mo IV O(S 2 PPr i 2 ) are monoclinic, space group P2 1 /n, with a ) 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
58
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 50 publications
8
58
0
Order By: Relevance
“…They are also amenable to conversion into a number of enzyme relevant EPR-active Mo(V) species [38,39]. Related hydrobis(3-isopropylpyrazolyl)(5-isopropylpyrazolyl)borate complexes are also accessible [40].…”
Section: Sulfido Ligand Complexesmentioning
confidence: 99%
“…They are also amenable to conversion into a number of enzyme relevant EPR-active Mo(V) species [38,39]. Related hydrobis(3-isopropylpyrazolyl)(5-isopropylpyrazolyl)borate complexes are also accessible [40].…”
Section: Sulfido Ligand Complexesmentioning
confidence: 99%
“…Several model systems for oxotransferases have been developed in order to better understand the reactivity of the molybdenum cofactors and the mechanisms of oxygen atom transfer. [18][19][20][21][22][23][24][25] The general mechanism proposed for the oxygen atom transfer includes a transition state where the molybdenum atom and the substrate are bridged by the oxygen atom that is either entering or leaving the coordination sphere of the molybdenum atom. The redox potentials, and thus potential reactivity/catalytic activity as well as substrate specificity of the enzymes (and model systems) are expected to be considerably influenced by the direct coordination environment of the molybdenum atom.…”
Section: Introductionmentioning
confidence: 99%
“…FDH catalyzes the oxidation of formate to CO 2 and a detailed description of the important biological processes that control the different chemical properties of molybdenum and tungsten to tune the reactivity, substrate specificity and metabolic role of FDHs has appeared recently. 56,57 A re-evaluation 68 of the previous X-ray structural analysis 69 of Mo-FDH active site showed that the [70][71][72][73] The usual problem of redox and hydrolysis reactions of Mo IV S units that leads to the formation of polynuclear complexes was avoided by use of sterically demanding tridentate ligands. However, use of nondithiolene ligands does not mimic the MPT ligand present in the active site.…”
Section: Perspectivementioning
confidence: 99%